Dynamic changes in ABA content in water-stressed Populus nigra: effects on carbon fixation and soluble carbohydrates. (2nd February 2019) - Brunetti, Cecilia; Gori, Antonella; Marino, Giovanni; Latini, Paolo; Sobolev, Anatoly P; Nardini, Andrea; Haworth, Matthew; Giovannelli, Alessio; Capitani, Donatella; Loreto, Francesco; Taylor, Gail; Mugnozza, Giuseppe Scarascia; et al.
Abstract: Background and Aims: Hydraulic and chemical signals operate in tandem to regulate systemic plant responses to drought. Transport of abscisic acid (ABA) through the xylem and phloem from the root to shoot has been suggested to serve as the main signal of water deficit. There is evidence that ABA and its ABA-glycosyl-ester (ABA-GE) are also formed in leaves and stems through the chloroplastic 2-C-methylerythritol-5-phosphate (MEP) pathway. This study aimed to evaluate how hormonal and hydraulic signals contribute to optimize stomatal ( g s ), mesophyll ( g m ) and leaf hydraulic ( K leaf ) conductance under well-watered and water-stressed conditions in Populus nigra (black poplar) plants. In addition, we assessed possible relationships between ABA and soluble carbohydrates within the leaf and stem. Methods: Plants were subjected to three water treatments: well-watered (WW), moderate stress (WS1) and severe stress (WS2). This experimental set-up enabled a time-course analysis of the response to water deficit at the physiological [leaf gas exchange, plant water relations, ( K leaf )], biochemical (ABA and its metabolite/catabolite quantification in xylem sap, leaves, wood, bark and roots) and molecular (gene expression of ABA biosynthesis) levels. Key Results: Our results showed strong coordination between g s, g m and K leaf under water stress, which reduced transpiration and increased intrinsic water use efficiency (WUEint ). Analysis of gene expression of 9- cis -epoxycarotenoid dioxygenase ( NCED ) and ABA content in different tissues showed a general up-regulation of the biosynthesis of this hormone and its finely-tuned catabolism in response to water stress. Significant linear relationships were found between soluble carbohydrates and ABA contents in both leaves and stems, suggesting a putative function for this hormone in carbohydrate mobilization under severe water stress. Conclusions: This study demonstrates the tight regulation of the photosynthetic machinery by levels of ABA in different plants organs on a daily basis in both well-watered and water stress conditions to optimize WUEint and coordinate whole plant acclimation responses to drought.